Time to first childbirth and its predictors among reproductive-age women in Ethiopia: survival analysis of recent evidence from the EDHS 2019 - Kitaw, Tegene Atamenta; Haile, Ribka Nigatu (Frontiers in Reproductive Health, 2023)
Abstract Background: Being a mother for the first time is the most significant event in a woman's life. "Age at first birth" refers to the age of a mother in years when she gave birth to her first child. The age of first childbirth has physical, economic, and social implications. However, little has been known so far in Ethiopia. Thus, this study sought to determine time to first childbirth and its predictors at the national level. Methods: The data were extracted from EDHS 2019 using STATA version 17 software. 8,885 weighted sample of reproductive-age women (15–49 years) were included in this study. A Kaplan Meier survivor curve was computed to estimate the time of first childbirth. A Log-rank test was used to compare the difference in survival curves. Akaike information criteria and Bayesian information criteria were computed to select the appropriate survival model for the data. Weibull accelerated failure time model with no frailty distribution was used to identify significant predictors. Results: The overall median survival time to first childbirth was 18 years. The significant predictors of time to first childbirth are mother educational level (primary education [ϕ = 1.036, 95CI:1.011,1.063], secondary and above educational [ϕ = 1.154,95CI: 1.118,1.191]), knowledge of any contraceptive method (know at least one [ ϕ = 1.051, 95CI:1.006,1.101]) and media exposure [ϕ=1.048, 95CI:1.011, 1.086]. Conclusion: The median survival time to first childbirth was 18 years, which is lower than the optimal age for first childbirth (late 20 and early 30 years). The timing of first childbirth in Ethiopia is mainly influenced by women's educational level, knowledge of contraceptive methods, and exposure to media. Thus, exposing women to educational materials and other awareness-creation campaigns regarding the consequences of early first childbirth and strategies to improve women's knowledge of contraceptive methods is highly recommended. Keywords: Childbirth, Predictors, Ethiopia.